Infant Development under 6 Months Old in a Family with Smoking Habit - Rufina Adelia Widyatama; Irwanto Irwanto; Dwi Susanti (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2021)
Introduction: Fastest developmental period of infants is on their first six months of life. However, smoking is a habit in Indonesia, done mostly by adult male (47.5%) on 30-34 years old group (33.4%) which can harm others, especially their family. Secondhand smoke, defined as environmental smoke that contains more than 4,000 dangerous chemicals, is the major cause of cigarette exposure, and home is the main place where children get exposed. Exposure of secondhand smoke can affect fetal brain, specifically on neurodevelopment stage, which can affect infant development.Methods: This study used analytic observational with cross sectional approach. Sampling method of the study was cluster sampling. This study involved 103 subjects who came to the selected primary health center. Data of smoking family was collected by interview, and infant’s development examination was done by the screening tool Pre-Screening Development Questionnaire (KPSP). Data were analyzed by chi-square correlation test between smoking habit and infant's development.Results: Number of infants in families with smoking habit were dominant which exposed by father is dominant (28.1%), followed by exposure by father and other family members (25.2%), and other family members (7.8%). Infants that were not exposed by secondhand smoke tend to pass the development test (67.5%). There was no significant relationship between infant’s development and smoking family habit (p = 0.128).Conclusion: Although the correlation is insignificant, parents should consider family smoking habit due to infants’ health and development.